Use of radiation in medicine in the Asia-Pacific region - Sun, Zhonghua; Ng, K. (Singapore Medical Association, 2012)
Rapid technological developments in medicine have taken place in the Asia-Pacific region over the last decades. Radiology, in particular, has seen enormous growth with the latest medical equipment and practices being commonplace in this region. The use of radiation in medicine must be carefully considered with regard to the potential side effects, such as radiation-induced cancer. There are very limited published papers on the use of radiation in medicine in this region. Hence, in this paper, we present an overview of the use of radiation in medicine in the Asia-Pacific region.